Pagophilus Gray 1844 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Pagophilus Gray 1844 Pagophilus Gray 1844, Zool. Voy. H. M. S. "Erebus" and "Terror", Vol. 1: 3. Type Species: Phoca groenlandica Erxleben 1777 Synonyms: Callocephalus Heuglin 1874; Haliphilus J. E. Gray 1866; Pagomys Gray 1864; Pagophoca Trouessart 1904. Species and subspecies: 1 species: Species Pagophilus groenlandicus (Erxleben 1777) Discussion: Burns and Fay (1970), Rice (1977), McDermid and Bonner (1975), Gromov and Baranova (1981), King (1983), and Wyss (1988) considered Phoca , Pusa , Histriophoca , and Pagophilus a monophyletic group. Cladistic analysis based on morphology and mtDNA reveal two clades, Pagophilus + Histriophoca and Phoca + Pusa + Halichoerus (Carr and Perry, 1998; Mouchaty et al., 1995; Muizon, 1982 b Perry et al., 1995; Rice, 1998). Burns and Fay (1970) and McDermid and Bonner (1975) argued that these differences should be recognized only at the subgeneric level. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 599, DOI: 10.5281/zenodo.7316519